(untitled) (KULT_online, 2019)
The historical textbook Beyond Balkanism: The Scholarly Politics of Region Making isn‘t just another book on the popular stereotypical discourse about the Balkans. Rather, it is a critical examination of the intellectual interest in the region from the 19th century onward. Diana Mishkova‘s extensive study concentrates on the ways various generations of scholars defined the Balkans, in order to inspect political usage of academic projects. By focusing on intra-regional geopolitical stakes and cross-border interactions, Mishkova changes the usual perception of the Balkans as a postcolonial space. With a fresh approach to the complicated notion of balkanism and a more than respectable corpus of critical literature, this research builds a basis for the further development of Area Studies in general.